Intraoperative Events in Liver Transplantation Using Donation After Circulatory Death Donors. Issue 12 (18th October 2019) - Chadha, Ryan M.; Croome, Kristopher P.; Aniskevich, Stephen; Pai, Sher‐Lu; Nguyen, Justin; Burns, Justin; Perry, Dana; Taner, C. Burcin
Abstract : Liver grafts from donation after circulatory death (DCD) are a source of organs to decrease wait‐list mortality. While there have been lower rates of graft loss, there are concerns of an increased incidence of intraoperative events in recipients of DCD grafts. We aim to look at the incidence of intraoperative events between recipients of livers from DCD and donation after brain death (DBD) donors. We collected data for 235 DCD liver recipients between 2006 and 2017. We performed a 1:1 propensity match between these patients and patients with DBD donors. Variables included recipient age, liver disease etiology, biological Model for End‐Stage Liver Disease (MELD) score, allocation MELD score, diagnosis of hepatocellular carcinoma, and year of transplantation. DCD and DBD groups had no significant differences in incidence of postreperfusion syndrome ( P = 0.75), arrhythmia requiring cardiopulmonary resuscitation ( P = 0.66), and treatments for hyperkalemia ( P = 0.84). In the DCD group, there was a significant increase in amount of total intraoperative and postreperfusion blood products (with exception of postreperfusion packed red blood cells) utilized ( P < 0.05 for all products), significant differences in postreperfusion thromboelastography parameters, as well as inotropes and vasopressors used ( P < 0.05 for all infusions). There was no difference in patient ( P = 0.49) and graft survival ( P = 0.10) at 1, 3, and 5 years. In conclusion, DCD grafts compared with a cohort of DBD grafts have a similar low incidence of major intraoperative events, but increased incidence of transient vasopressor/inotropic usage and increased blood transfusion requirements. This does not result in differences in longterm outcomes. While centers should continue to look at DCD liver donors, they should be cognizant regarding intraoperative care to prevent adverse outcomes.